2013
DOI: 10.4103/0300-1652.108889
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood haemoglobin and ferritin concentrations in newborns of anaemic and non-anaemic mothers in Lagos, Nigeria

Abstract: Background:Pre-delivery haemoglobin and serum ferritin concentrations of anaemic and non-anaemic mothers were determined, and cord blood haemoglobin and serum ferritin concentrations of their newborns were compared. This is to establish the mean values for pre-delivery haemoglobin and serum ferritin concentrations of anaemic and non-anaemic mothers and the cord blood haemoglobin and serum ferritin concentrations of their newborns at term.Materials and Methods:A case–control study was done involving 142 pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 14 publications
(14 reference statements)
6
16
2
Order By: Relevance
“…Mean gestational age was 38.35 ± 0.8SD. It was comparable to the study done by Paulo et al, Betelihem et al, 16 Adewuni et al, 17 Hadipour et al 15 and Jie Shao et al 18 where all the participating women were in their their third trimester with period of gestation >-37 weeks.…”
Section: Discussionsupporting
confidence: 86%
“…Mean gestational age was 38.35 ± 0.8SD. It was comparable to the study done by Paulo et al, Betelihem et al, 16 Adewuni et al, 17 Hadipour et al 15 and Jie Shao et al 18 where all the participating women were in their their third trimester with period of gestation >-37 weeks.…”
Section: Discussionsupporting
confidence: 86%
“…The overall anemia prevalence among newborn babies was 25% (95% CI: 18.9, 31.1%). According to WHO recommendation our finding showed a moderate public health problem in the study area [15]. Due to reduced oxygen-carrying capacity; anemia has a still serious public health implication that leads to newborn morbidity and mortality [16].…”
Section: Discussionmentioning
confidence: 99%
“… 14 Our results, therefore, agree with previous studies on the ferritin level of pregnant and non-pregnant subjects, which concluded that iron deficiency did not have a high prevalence in Nigeria. 15 , 16 Of importance, in this study, however, is the observation of different degrees of iron deficiency and sideropenia in which some women who had no anemia were found with iron deficiency. This may stem from the fact that iron deficiency occurs in stages, and the women observed with sideropenia may be in the early stage where serum ferritin is significantly reduced with no obvious change in the hemoglobin level.…”
Section: Discussionmentioning
confidence: 82%